Two Faces of a Mom: Student Mothers’ Lived Experiences in a State University - Andres, Karen P. (Future Science / FSH-PH Publications, 2021)
This phenomenological study explored the lived experiences, challenges, and complicated life of 12 mothers who are pursuing their collegiate degree in a state university while rearing and taking care of their children. Participants met the inclusion criteria of a student mother, which includes (1) a bonafide student of a tertiary state institution; (2) a biological mother; (3) residing with her child/children; and (4) willingness to participate in the inquiry. Three major themes emerged in the participants’ lived experiences, which include (1) hustles and bustles of student mothers’ life; (2) driving factors of student mothers; and (3) coping mechanisms of two-faced mothers. The findings revealed that the participants faced adversities and struggles as a mother and as students and remained more steadfast and more resilient in fulfilling their dreams to finish their collegiate degree and receive a university diploma. The lived experiences of the student mothers have established implications to policies in the university, which involves the creation of daycare centers inside the campus for the children of student mothers as well as the conduct of psychosocial debriefing and stress reduction programs by the Gender and Development (GAD) office for the student mothers.